REGIME-TECHNOLOGICAL PARAMETERS FOR ESTIMATION OF AUTHENTICITY OF CALCULATION OF GAS BALANCE OF GAS-TRANSPORTATION SYSTEM - , В. А., М. Б. (Municipal economy of cities. Series: «Economy science», 2017)
Are identified the problems of choice and ranging of regime-technological parameters influencing on the error of the calculation of gas balance in the gas-transportation system.Collected and systematized the daily and monthly data about the receipt of gas to the gas-transportation system, used gas, volume of the transported gas, gas expenses on productively-technological necessities, charges of gas depending on time, change of gas supply in a pipeline. Were analysed monthly data for three years. For each of these factors are expected the values of balance of gas and error of calculation of the gas balance. Аre used the methods of mathematical statistics for research of dependence the error of calculation of gas balance for each of these parameters. For the estimation of dependence of size the error of the calculation of gas balance from regime-technological parameters the methods of cross-correlation analysis of accumulated data were applied. For every regime-technological parameter the values of coefficients of correlation are expected, that gave an opportunity to set a list and meaningfulness of influence of each of parameters on the size of error of calculation of gas balance in the gas-transportation system Keywords: the gas-transportation system, the balance of gas, regime-technological parameters, the methods of mathematical statistics.